The Effect of School Culture, and Stress Management on Teacher’s Organizational Commitment in Senior High School in District of Padang Lawas - Siregar, Astri Novia (Holistic Science, 2023)
This study aimed to determine: (1) the effect of school culture on stress management, (2) the effect of school culture on teacher’s organizational commitment, (3) the effect of stress management on teacher’s organizational commitment. This study uses quantitative methods, the model used is the path analysis with inferential data analysis techniques. The population in this study are all teachers of senior high school in the district of Padang Lawas, amounting to 214 teachers. The research sample was determined by using a proportional stratified random sampling technique to obtain a sample of 137 teachers. The research instrument used for data collection was a questionnaire. The results of this study found: (1) there is a direct and significant effect of school culture on the management of work stress with correlation coefficient = 0,253 with a contribution of direct effect of 6%, (2) there is a direct and significant effect of school culture on teachers' organizational commitment with correlation coefficient = 0,233 with a contribution effect of 5%, (3) there is a direct and significant effect of work stress management on organizational commitment of teachers are direct and significant effect of stress management on organizational commitment of teachers working with a correlation coefficient of 0,217 with a contribution of R = the effect of 5%